2011
DOI: 10.1121/1.3605672
|View full text |Cite
|
Sign up to set email alerts
|

Phonation threshold pressure: Comparison of calculations and measurements taken with physical models of the vocal fold mucosa

Abstract: In an important paper on the physics of small amplitude oscillations, Titze showed that the essence of the vertical phase difference, which allows energy to be transferred from the flowing air to the motion of the vocal folds, could be captured in a surface wave model, and he derived a formula for the phonation threshold pressure with an explicit dependence on the geometrical and biomechanical properties of the vocal folds. The formula inspired a series of experiments [e.g., R. Chan and I. Titze, J. Acoust. So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2012
2012
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 18 publications
0
14
0
1
Order By: Relevance
“…This prediction is not consistent with Chan and Titze's 2006 measurements, 6 where the linear trend of the threshold pressure data clearly does not approach zero. As shown in our earlier work with Titze's surface wave model, 7 the key to resolving this discrepancy is to introduce a parameterization of the entrance loss coefficient that includes an inverse dependence on the glottal half-width. It is shown that this parameterization may be readily incorporated into the two-mass model of Ishizaka and Flanagan.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This prediction is not consistent with Chan and Titze's 2006 measurements, 6 where the linear trend of the threshold pressure data clearly does not approach zero. As shown in our earlier work with Titze's surface wave model, 7 the key to resolving this discrepancy is to introduce a parameterization of the entrance loss coefficient that includes an inverse dependence on the glottal half-width. It is shown that this parameterization may be readily incorporated into the two-mass model of Ishizaka and Flanagan.…”
Section: Resultsmentioning
confidence: 99%
“…This situation was explored further in Ref. 7, where Lucero's suggestion 27 of using Poiseuille's approach to describe viscous effects of the flowing air within the glottis to explain the upward trends was analyzed. There it was shown that Poiseuille's approach to viscous effects should also lead to upward trends in Chan and Titze's 2006 measurements at small glottal widths.…”
Section: Results For Threshold Presssuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Note that Zhang and Luu (2012), which used a similar 1D flow model but without accounting for the glottal flow viscous loss, also reported a stronger fluidstructure interaction in their numerical model than in their experiment. These issues need to be further explored in future studies, using more accurate vocal fold material properties data, a better representation of the experimental setup, and gradually refined flow models [e.g., including the glottal channel curvature effect, or using more accurate models of the glottal flow viscous loss (Fulcher and Scherer, 2011)]. Such studies would help to reveal the effects on phonation of the various flow features that are neglected in 1D flow models.…”
Section: Discussionmentioning
confidence: 99%